Polyherbal–antibiotic synergy: a review on mechanistic insights into polyphenols, flavonoids, alkaloids, and terpenoids for enhancing antimicrobial efficacy - Neelakshi Sharma; Bipul Nath; Trishna Das; Manas Jyoti Kapil; Amaryllis Langbang (Creative Pharma Assent, 2026)
Background: Antimicrobial resistance (AMR) is one of the most important threats to global public health, accelerating as conventional antibiotics lose efficacy. Pathogens such as Staphylococcus aureus, Pseudomonas aeruginosa, Escherichia coli, and Klebsiella pneumoniae use a variety of resistance mechanisms, including enzymatic drug degradation, efflux pump activation, and biofilm formation. The declining pipeline of newly approved antibiotics highlights the need for alternative and adjunctive therapeutic strategies. Methodology: This review critically summarizes studies that analyze polyherbal–antibiotic combinations and their synergistic antimicrobial effects. A systematic review of recent literature on the role of phytochemicals, including alkaloids, flavonoids, terpenoids, tannins, and polyphenolic compounds, in potentiating antibiotic efficacy and reducing antibiotic resistance was conducted. Results and Discussion: Integrative synergetic interactions were strongly evidenced between antibiotics and plant-derived phytochemicals. Epigallocatechin gallate (EGCG) synergizes with β-lactam for common resistant strains, and berberine inhibits efflux pumps to enhance antibiotic activity. A wide range of flavonoids and polyphenolic extracts have been reported to exhibit antimicrobial activity, with mechanisms involving membrane disruption, biofilm inhibition, and interference with quorum-sensing pathways, thereby promoting multifaceted action. Conclusion: Synergy between polyherbal treatment and antibiotics is an innovative approach to combat AMR and should be prioritized. This approach highlights various leads for future antimicrobial therapeutics by combining traditional ethnopharmacological knowledge with innovative pharmaceutical paradigms.